Molecular docking and simulation of Curcumin with Geranylgeranyl Transferase1 (GGTase1) and Farnesyl Transferase (FTase) - Subramani, Parasuraman Aiya (Bioinformation, 2015)
Protein prenylation is a posttranslational modification that is indispensable for translocation of membrane GTPases like Ras, Rho, Ras etc. Proteins of Ras family undergo farnesylation by FTase while Rho family goes through geranylgeranylation by GGTase1. There is only an infinitesimal difference in signal recognition between FTase and GGTase1. FTase inhibitors mostly end up selecting the cells with mutated Ras proteins that have acquired affinity towards GGTase1 in cancer microcosms. Therefore, it is of interest to identify GGTase1 and FTase dual inhibitors using the docking tool AutoDock Vina. Docking data show that curcumin (from turmeric) has higher binding affinity to GGTase1 than that of established peptidomimetic GGTase1 inhibitors (GGTI) such as GGTI-297, GGTI-298, CHEMBL525185. Curcumin also interacts with FTase with binding energy comparable to co-crystalized compound 2-[3-(3-ethyl-1-methyl-2-oxo-azepan-3-yl)-phenoxy]-4-[1-amino-1-(1-methyl-1h-imidizol-5-yl)-ethyl]-benzonitrile (BNE). The docked complex was further simulated for 10 ns using molecular dynamics simulation for stability. Thus, the molecular basis for curcumin binding to GGTase1 and FTase is reported.